Finite-Differences-Based Solvers for Wave Propagation in Dielectric Waveguides and Rings - Simsek, Ergun (IEEE, 2025)
Dielectric waveguides and ring resonators are foundational structures in photonics, enabling applications such as optical frequency comb generation, filtering, and sensing. This work presents a complete formulation to analyze electromagnetic wave propagation in these structures, incorporating the shooting method to accurately calculate propagation constants, effective indices, and modal fields. With the help of the coupled-mode theory, we investigate the transmission spectrum of a Si3N4 waveguide coupled to a Si3N4 ring under the critical resonance condition. Our numerical results agree with the ones generated with COMSOL Multiphysics.
2025 International Applied Computational Electromagnetics Society Symposium (ACES), 18-21 May 2025, Orlando, FL, USA
Keywords: Optical ring resonators; Photonics; UMBC Computational Photonics Laboratory; Optical waveguide theory; Optical harmonic generation; Resonant frequency; Resonance; Propagation constant; Electromagnetic waveguides; Dielectrics; Sensors